2019
DOI: 10.5586/asbp.3637
|View full text |Cite
|
Sign up to set email alerts
|

Weed vegetation of arable land in Slovakia: diversity and species composition

Abstract: Arable fields are among the most widespread habitats in Slovakia, but recently, there have been no studies regarding species composition and structure of weed vegetation in these fields. Therefore, we studied the structure of arable weed vegetation and detected α- and β-diversity. The dataset of 507 phytosociological relevés in different crop types contains 407 plant taxa in 46 plant families. Native plants dominated over aliens, archaeophytes dominated over neophytes, and 14 plants belonged to invasive taxa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Kolářová et al (2013b) also report the highest incidence of endangered weed species in cereals, especially spring. In Slovakia, Májeková et al (2019) confirm the priority occurrence of endangered weeds in cereals and at least in root crops. This is associated with the fact that endangered weeds mostly include therophytes, with winter or early spring germination regime having its optimum development in cereals.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Kolářová et al (2013b) also report the highest incidence of endangered weed species in cereals, especially spring. In Slovakia, Májeková et al (2019) confirm the priority occurrence of endangered weeds in cereals and at least in root crops. This is associated with the fact that endangered weeds mostly include therophytes, with winter or early spring germination regime having its optimum development in cereals.…”
Section: Resultsmentioning
confidence: 58%
“…It will therefore depend on the specific conditions of the habitat and the intensity of farming. Extensively cultivated fields provide refuges for the survival of rare species (Májeková et al 2019). The number of Red List species in the vegetation is higher in complex than in simple landscapes and decreased when the percentage of arable land cover increased (Roschewitz et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Just as found in this survey, species richness differed substantially among the fields, ranging from 0 to 49 species per relevé. Another arable land survey, Májeková et al (2019) present 407 plant taxa found on arable land in 46 plant families. The most frequent taxa were T. inodorum (74%), Cirsium arvense (L.) Scop.…”
Section: Landscape-level Weed Diversitymentioning
confidence: 99%
“…National weed surveys have been conducted in many countries, including among others Spain (Cirujeda et al 2011), Hungary (Novák et al 2012), Germany (De Mol et al 2015), Denmark (Andreasen et al 2018) and Slovakia (Májeková et al 2019). The major aim of those surveys has usually been to get updated information on the species composition of weed communities and the affecting factors.…”
Section: Introductionmentioning
confidence: 99%